Konsep Ketuhanan Filsafat Saiva Advaita - Ni Made Evi Kurnia Dewi; Komang Heriyanti (Sanjiwani: Jurnal Filsafat, 2020)
Trust is an important element in understanding a religion,but trust is not enough to answer the question about God (Siva) logically.Saiva Advaita's philosophy is here to answer all questions about Lord Siva logically. "Experience and faith" began to be included in the terminology of philosophy, this is done to answer all doubts about God.Saiva Advaita is generally known as Trika philosophy.Trika philosophy emphasizes three important aspects of the Godhead consisting of Siva (Para), Sakti (Parapara), and Soul (Apara). Para refers to Siva or Brahman.Para means the best, the highest, the Most Great, Kausa Prima, pure awareness.Para is the Supreme Self consciousness, which is referred to as Brahman.Parapara is an absolute state and relativity known as Sakti.Sakti is the embodiment of the power of Siva.Apara is a soul. Apara refers to nara (human),a true spiritual person.Brahman and soul (apara) are two substances in common, no separate identities or differences are all one.